2015
DOI: 10.1039/c5ra18806g
|View full text |Cite
|
Sign up to set email alerts
|

A porous aerogel nanocomposite of silver nanoparticles-functionalized cellulose nanofibrils for SERS detection and catalytic degradation of rhodamine B

Abstract: Herein, cellulose nanofibrils (CNFs) were functionalised with silver nanoparticles (AgNPs) via a green in situ hydrothermal synthesis approach. The produced nanocomposites were used for the detection and catalytic degradation of rhodamine B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 39 publications
(44 reference statements)
1
17
0
Order By: Relevance
“…Some examples of Ag ENMs used for polluted water treatments are reported in Table 2, pointing out AgNP size and supporting the existence of synergic effects in some cases [61,75,[109][110][111][112]. A large number of innovative hybrid materials with a synergetic or complementary behavior were obtained using Ag-based photocatalysts.…”
Section: Agnps For Water Pollution Monitoring and Treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Some examples of Ag ENMs used for polluted water treatments are reported in Table 2, pointing out AgNP size and supporting the existence of synergic effects in some cases [61,75,[109][110][111][112]. A large number of innovative hybrid materials with a synergetic or complementary behavior were obtained using Ag-based photocatalysts.…”
Section: Agnps For Water Pollution Monitoring and Treatmentmentioning
confidence: 94%
“…Chook's group adopted this approach for the design of a porous AgNPs/CNF aerogel nanocomposite, which revealed superb performances in detecting and catalyzing the degradation of rhodamine B from water solutions, in the presence of NaBH 4 [112,187]. Similarly, Han et al proposed the reductant-free synthesis of AgNPs-doped cellulose microgels for mediating the reduction of nitrophenols, always by means of NaBH 4 [188].…”
Section: Cellulose Doping With Agnps Generated In Situmentioning
confidence: 99%
“…As such AgNPs can act as a suitable catalyst for the reduction of 4-NP. Other studies have also found that polysaccharide-based AgNPs have a significant catalytic activity to reduce pollutants such as 4-NP, methyl orange, methylene blue, and rhodamine B in the presence of NaBH 4 medium [15,152].…”
Section: Catalysis Properties Of Polysaccharide-based Agnpsmentioning
confidence: 99%
“…To date, SERS of AuNPs and AgNPs has been extensively studied [3,4,20,21]. The performance of AuNPs/nanocellulose or AgNPs/nanocellulose nanocomposites as SERS substrates has also been reported in several studies [22,23,24,25,26,27,28,29]. For example, Limei Tian et al [22] described a gravity-assisted filtration method for biosynthesized bacterial nanocellulose based SERS substrate fabrication.…”
Section: Introductionmentioning
confidence: 99%